Most Physically Educated Contest. Issue 3 (24th March 2018) - Mercier, Kevin; Howard, Thomas
Abstract : It is seldom that the accomplishments of secondary physical education students are celebrated. The Most Physically Educated Contest was developed to allow students from several school districts to gather for appropriate competition and to display the characteristics of physical literacy attained from participation in high-quality physical education programs. The purpose of this article is to share with readers the process of developing, organizing and executing a Most Physically Educated Contest so that others can replicate the event in their own setting. Students participated in the following events, with assessments aligned with the National Standards: (1) written essay, (2) PACER test, (3) push-up assessment, (4) badminton task, and (5) basketball task. All of the steps from initial planning to awards, including keys to success, schedule of events, and the awards ceremony, are presented.